CO-DESIGN: CATALYST FOR INCLUSION IN THE DESIGN PROCESS - Akach, Joyce Akinyi; Osanjo, Lilac; Maina, Samuel (Machakos University Press, 2021)
Older persons are considered custodians of culture and the knowledge they possess need to be preserved for posterity. Is there a good approach to extract this knowledge and package it for posterity? This paper is an analysis of co-design approach and how it can be used to induce, capture and collect the knowledge, ideas, wishes and hopes of a group of older persons for the preservation of a cultural museum. Through the use of co-design tools, the older persons provided visual narratives that were used to redesign RAMA Cultural Centre in Homabay County. A field survey in Homabay County in August 2016 revealed that RAMA Cultural Centre had many cultural artifacts that were not well preserved and were at a great risk of destruction from environmental factors such as pests, molds and theft. Besides these, the older persons who were the curators of the cultural museum, had not been able to successfully integrate the youth in the management of the museum leading to a possible extinction of this indigenous knowledge. The methodology describes the co-design tools and how they were applied to include the older persons in the design of the RAMA Cultural Museum. The discussion is on co-design approach for novice researchers, possibilities and challenges of co-designing with older persons and concludes with learning on how to effectively co-design with non-designers, specifically older persons, tapping into their dreams and aspirations so as to inform as well as inspire the design development process.
Keywords: Co-design; Co-create; Participatory design; Probes; Prototypes; Generative design tools; Older Persons